THU0300 Central nervous system involvement in granulomatosis with polyangiitis (WEGENER) in a large series of patients with anca-associated vasculitides (AAV).revas STUDY-GEAS-SEMI. (15th June 2017) - Solans-Laqué, R; Rodriguez-Carballeira, M; Castillo, M; Fraile, G; Rios, J; Solanich, X; Martinez-Valle, F; Saez, L; Pasquau, F; Fonseca, E
Abstract : Background: GPA is a necrotizing systemic vasculitis that usually involves ENT, lung and kidneys. Neurological manifestations appear in 25–50% of patients, usually involving peripheral nervous system. CNS involvement, has been reported in only 7–11% of cases Objectives: to describe the clinical features and outcome of patients with GPA and CNS involvement in a large series of patients with AAV Methods: multicenter retrospective-longitudinal study that encompassed patients diagnosed with AAV between Jan 1995 and Nov 2014 in 21 Centres from Spain (REVAS Study). Statistical anlysis was performed using SSPS vs20 package Results: 455 patients (188 GPA, 167 MPA and 100 EGPA) were included. Mean age at diagnosis was 55.7±17.2y. ANCA were positive in 86.8% of cases (35.8% C-ANCA, 51% P-ANCA). Median time to diagnosis was 4 weeks (IQR 10). Median follow-up time was 80 months (IQR 105). Neurological involvement was documented in 156 (34.5%) patients, but only 33 (7.3%) presented CNS involvement at disease onset. From those patients, 20 (60.6%) had GPA. Mean age at diagnosis of patients with GPA and CNS involvement was 51.1±16.7y. ANCA were positive in all cases (15 C-ANCA-PR3, 5 P-ANCA-MPO). Headache was the main neurological symptom (60%) followed by sensory (45%) and motor impairment (35%). MRI and/or angio-CT scan were performed in all cases. Cerebral ischaemic lesions were observed in 10 patients, and granulomatous lesions in 9, including pachymeningitis (n=6), spinal cord pachymeningitis (n=2) and isolated granulomatous lesions (n=1). Lumbar puncture was performed in 8 (40%) patients and revealed CSF abnormalities in 70. Diagnosis was confirmed by meningeal biopsy (n=2), ENT biopsies (n=5) and renal biopsy (n=2) in patients with CNS granulomatous lesions, and by renal, pulmonary or peripheral nerve biopsy in patients with CNS ischemic lesions. Headache was predominant in patients with granulomatous lesions, while sensory and motor impairment were predominant in patients with ischemic lesions. Mean BVAS at disease onset was 29.2±9.7, significantly higher than in GPA total cohort (18.2±9.2). Renal involvement was more common in patients with ischaemic lesions than in those with granulomatous (80% vs. 40%, p<0.001), and ENT involvement in patients with granulomatous forms (70% vs. 50%, p<0.005). Most patients (70%) received oral CF for induction therapy. Two patients received rituximab. For maintenance therapy, 25% of patients received AZA, 20% MMF and the remaining CF. 70% of patients received TM-SX. During follow-up, 58.8% and 40% of patients developed bacterial and opportunistic infections, respectively. Infections were related to oral CF therapy (p=0.029). Long-term neurological sequelae were noted in patients with ischaemic lesions (40%) and spinal cord pachymeningitis (100%) Conclusions: Patients with GPA and CNS involvement have more severe disease at presentation and more treatment-related side effects than patients without CNS involvement. Long-term neurological sequelae are more frequent in patients with ischaemic lesions and spinal cord pachymeningitis Disclosure of Interest: None declared